Nitrogen fertilization and irrigation depths in yellow passionfruit. I. Yield and fruit quality - Carvalho, Almy Junior Cordeiro de; Martins, Donivaldo Pedro; Monnerat, Pedro Henrique; Bernardo, Salassier (Pesquisa Agropecuaria Brasileira, 2000)
A field experiment was carried out, in Campos dos Goytacazes, RJ, Brazil, from December, 1995 to June, 1997, to evaluate the effect of nitrogen fertilization, under different irrigation depths, on yield and fruit quality of yellow passionfruit. Four nitrogen levels (50, 250, 450 and 650 g plant-1 year-1 of N) were tested, using urea as the source of N, under six irrigation depths (0, 25, 50, 75, 100 and 125% of ET0 - reference crop evapotranspiration for grass), at 4 x 6 factorial scheme with three replications. A dripping irrigation system was used. There was no yield response due to increasing nitrogen levels when 0, 25, 100 and 125% of ET0 were applied. Maximum fruit yield (41.3 ton ha-1) was obtained when 290 g plant-1 year-1 of N was applied under an irrigation depth close to 75% of ET0, which corresponded to a total of 1,293 mm of applied water (irrigation + effective rainfall). Nitrogen fertilization influenced the number of fruit and did not show any effect on either average weight or other fruit qualitative characteristics. Irrigation depth had great influence on fruit yield, average weight, length and diameter.